Protective effects of phytochemicals of Capparis spinosa seeds with cisplatin and CCl4 toxicity in mice. (April 2019) - Tir, Meriam; Feriani, Anouar; Labidi, Arbia; Mufti, Afoua; Saadaoui, Ezzeddine; Nasri, Nizar; Khaldi, Abdelhamid; El Cafsi, Mhammed; Tlili, Nizar
Abstract: The phenolic compound content and the beneficial effects of Capparis spinosa seed extracts (CSSE) against the toxicity induced using cisplatin and CCl4 treatment were studied. The amounts of total phenolics, flavonoids and condensed tannins were 83 mg gallic acid equivalents, 92 mg rutin equivalents, and 1 mg tannic acid equivalents/g d.w., respectively. Results showed that CSSE pretreatment restored the higher content of serum creatinine, urea and uric acid, and increased activities of aspartate aminotransferase, and alanine aminotransferase induced by cisplatin and CCl4 treatment. Furthermore, CSSE pretreatment decreased the protein carbonyls and malondialdehyde, and increased the activities of superoxide dismutase, catalase, and glutathione peroxidase. Histopathological studies confirmed that CSSE decreased the degree of tissues fibrosis. The results obtained confirmed the potential nutritional and medicinal benefits of C. spinosa and highlighted the potential use of the seeds as a source of bioantioxidants for the food and pharmaceutical industries. Highlights: Preliminary phytochemical analysis of methanol extracts of Capparis spinosa seeds. Biochemical analysis showed nephroprotective and hepatoprotective effects. Histopathological study suggested that the extracts protect against tissues fibrosis.